RESPONSE OF Jatropha curcas L. TO FUNGAL PATHOGENS IN SOUTHWESTERN NIGERIA (2015)
Cultivation of Jatropha curcas L. for production of biodiesel as an alternative source of energy is crucial for sustainable development in Nigeria. Pests and pathogens especially fungi have been reported to be a major constraint to commercial cultivation of J. curcas in Asia and some West African countries. However, this is yet to be fully investigated and documented in Nigeria. Fungal pathogens infecting J. curcas in southwestern Nigeria were therefore investigated. Two hundred plant samples were randomly collected from each of Ekiti, Lagos, Ogun, Ondo, Osun and Oyo states, Nigeria. Fungi were isolated from these samples and the isolates were identified using standard procedures. Pathogenicity tests of these organisms (n=12) were carried out on five J. curcas accessions (Ex-Basirika, Ex-Mbatdiya, Ex-Misau, Ex-Ibadan and Ex-Kano) in the screenhouse using Koch’s postulates. The experiment was laid out in a Completely Randomized Design (CRD) with four replicates. The accessions were also grown for three years on the field in Randomized Complete Block Design (RCBD) layout with four replicates. Data were collected on occurrence of fungal organisms. Disease intensity (incidence and severity) were recorded at weekly intervals for 16 weeks after inoculation. Field evaluation of disease incidence (%) and severity (1-5, ranging from no disease to highly susceptible) was carried out at three months interval for three years. Data were analysed using descriptive statistics and ANOVA at 0.05. Anthracnose, mildew, canker, dieback, fruit and root rots were common symptoms found on J. curcas in southwestern Nigeria. Colletotrichum gloeosporioides was the highest occurring fungal species in all the states with the highest occurrence (26.0 %) in Ekiti. Oidum jatrophae was the lowest with the least occurrence (7.1 %) in Lagos state. Colletotrichum gloeosporioides, Curvularia lunata, Fusarium oxysporum, Oidum jatrophae and Lasiodiplodia theobromae among the isolated fungi were pathogenic on Jatropha curcas in the screenhouse experiment. Reactions of the accessions to fungal diseases showed significant variations in disease incidence and severity. Susceptibility of accessions was in the order: Ex-Ibadan > Ex-Kano > Ex-Mbatdiya > Ex-Basirika > Ex- Misau (61.4 % > 59.5 % > 43.4 % > 37.4 % and > 28.3 %, respectively). Anthracnose was the most prevalent disease encountered, with maximum incidence in the screenhouse (26.6 %) and on the field (95.7 %). Disease intensity for Colletotrichum leaf anthracnose, L. theobromae collar rots, Cankers, Oidum mildew, shoot dieback and F. oxysporum root rots was 59.7 %, 26.5 % , 16.4 %, 41.9 %, 43.1 % and 38.9 % respectively. Five pathogenic and seven non-pathogenic fungi were isolated from Jatropha curcas in southwestern Nigeria. Colletotrichum gloeosporioides was the major isolated fungal pathogen and was the most virulent on Jatropha curcas. Ex-Misau was tolerant and it is therefore recommended for intensive cultivation.